THE ROLE OF GREEN FINANCING INPROMOTING SUSTAINABLE ECONOMIC DEVELOPMENT A QUALITATIVE STUDY - Syamsul Effendi; Manna Salwa; Siti Aisah; Sariya Saputri Siregar; Ajeng Pratiwi (Universitas Efarina, 2023)
In recent years, the global financial system has increasingly integrated environmental, social, and governance (ESG) principles to align economic progress with environmental sustainability. One of the most significant developments in this area is the emergence of green financing—a financial approach that channels investments towards environmentally friendly and climate-resilient projects. This study aims to examine the role of green financing in promoting sustainable economic development, focusing particularly on its implementation, benefits, and challenges within the context of developing countries like Indonesia.Using a qualitative descriptive method, the research combines literature analysis with in-depth interviews involving practitioners from Islamic financial institutions, environmental NGOs, and public policy experts. The findings reveal that green financing plays a pivotal role in supporting initiatives such as renewable energy, sustainable agriculture, and eco-friendly infrastructure. Additionally, the study highlights how green financial instruments like green bonds and green sukuk not only contribute to environmental goals but also offer long-term economic benefits through risk reduction and improved investor confidence.However, the implementation of green financing faces several barriers, including weak regulatory frameworks, limited financial literacy among stakeholders, and the lack of standard criteria for evaluating